Small cell neuroendocrine carcinoma: a case study in gynecologic cytopathology - Machado, Bruno Gomes (2015)
The present study shows the case of a 62 years old woman, whose only clinical data was a suspected cervical sarcoma. A liquid-based cytology and biopsies from the cervix and the endometrium were done and sent for diagnostic laboratory. The cytology showed numerous groups of a variable number of monotonous, small and round cells, having scarce cytoplasm in a diathesis background. The nuclei featured molding, hyperchromasia, “salt-and-pepper” chromatin and no nucleoli. Similar observations could be found with the biopsies, where atypical gland-like groups were also detected. This neoplasia showed positive immunostaining for neuron specific enolase, synaptophysin and cytokeratin (AE1/AE3 clone antibodies), and a proliferative activity demonstrated by the nuclear marker Ki67/Mib1 immunorreactivity. The cytological, histological and imunohistochemical findings were consistent with the diagnosis of a small cell neuroendocrine carcinoma. Of all the cervical tumors, this sort of malignancy is one of the rarest and has a very aggressive behavior, with poor prognosis and without effective treatment. Its cause may be related to the Human Papillomavirus infection, but this still remains in study.